Robustecimento do sistema de desenvolvimento de produtos em PME´s do setor eletroeletrônico em nível estratégico e operacional: aplicação em uma indústria da área de materiais elétricos de instalação - Joao Marcos Belisario Dantas (2006)
The new product development activities within small and medium companies is, in mostcases, informal and subjective. This is mainly due to the absence resources, in most caseshuman, in such companies. As the companies evolve their growth, or increase thetechnological level of their products, or try to innovate their products, greater is the need for amore effective internal organization of the product development activities. This need can benoticed both in terms of the process of development of a certain product and in the definitionof what the company should develop to advance over the market of a product in the short,mid and long term.In the face of such deficiency in this regard shown by the small and midium size companiesof the electro-electronic field, the overall aim of this research is the study of a method oforganization and systematization, both at strategic and operational level, to furtherstrengthen the new product development activities within small and medium Braziliancompanies of the electro-electronic and electric fixture materials field. Such study is ofutmost importance to help these companies promote the strengthening of their own systemof product development. To undertake this research it was necessary to work in the light ofthe state of art of the operational and strategic levels. As a result, the study also made itpossible an in-depth approach on the literature review about the themes of CostDeployment and Platforms Renewal somewhat not much explored in our country.To meet the general goal, interventions in one of the industries of this field were proposed.On this occasion it was used the method of platform renewal by means of the developmentof a strategy for the renewal of one of the current platforms of the company. Also, in two ofthe interventions, the Quality Function Deployment (QFD) and Cost Deployment were usedin projects of new products for the company. Next, a study was carried out on how themethods had contributed for such strengthening and its characteristics and results comparedto the current literature.The methodology adopted for the research was the action-research, since to meet the goalof the research it was necessary for the researcher to act on the company process.Among the most important conclusions of the work, we can highlight greater market view,and a systematic search for opportunities provided by the use of the platform renewal. Theneed to create a procedure for the platform renewal more suitable for the reality of the fieldwas a relevant conclusion. Difficulties experienced are due to the short time available,shortage of funds, and lack of quantitative data. At the operational level, the new PDPestablished proved to be very active mainly in regard to the formal attraction andunderstanding of the client voice, their preferences and perception. Also, during the processof concept establishment and use of multifunctional team there was a broadening of theknowledge and commitment of all members towards the project. Another relevant conclusionwas the need to adequate cost deployment, by adding aspects of technical difficulty of thecost reduction.